1999
DOI: 10.1103/physrevb.59.1497
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle relaxation dynamics in superconductors with different gap structures: Theory and experiments onYBa2Cu3

Abstract: Photoexcited quasiparticle relaxation dynamics are investigated in a YBa2Cu3O 7−δ superconductor as a function of doping δ and temperature T using ultrafast time-resolved optical spectroscopy. A model calculation is presented which describes the temperature dependence of the photoinduced quasiparticle population npe, photoinduced transmission ∆T /T and relaxation time τ for three different superconducting gaps: (i) a temperature-dependent collective gap such that ∆(T ) → 0 as T → Tc, (ii) a temperature-indepen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

53
457
5
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(516 citation statements)
references
References 36 publications
53
457
5
1
Order By: Relevance
“…Usually the anomalous T dependence of τ exp is observed in many gapped systems, for example, phaseordered systems showing an energy gap opening in the electron band below the transition temperature T c . It has been found that a wide variety of superconductors [1][2][3][4][5][6][7][8][9][10][11][12][13] and density-wave compounds [14][15][16][17][18][19] show diverging behavior of τ exp near T c , as confirmed by femtosecond time-resolved optical spectroscopy. 1,4,5,[7][8][9][10][11][12][13][14][15][16][17]19 The divergence of τ exp in these gapped systems is believed to result from a recursive energy transfer between electrons and phonons.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Usually the anomalous T dependence of τ exp is observed in many gapped systems, for example, phaseordered systems showing an energy gap opening in the electron band below the transition temperature T c . It has been found that a wide variety of superconductors [1][2][3][4][5][6][7][8][9][10][11][12][13] and density-wave compounds [14][15][16][17][18][19] show diverging behavior of τ exp near T c , as confirmed by femtosecond time-resolved optical spectroscopy. 1,4,5,[7][8][9][10][11][12][13][14][15][16][17]19 The divergence of τ exp in these gapped systems is believed to result from a recursive energy transfer between electrons and phonons.…”
Section: Introductionmentioning
confidence: 90%
“…It is based on the assumption that photoexcited carrier relaxation in gapped systems is regulated by the anharmonic slow decay of phonons. 1,23 By the absorption of a pump laser photon, electrons in the valence band are excited far above the initial states, and they rapidly accumulate in the upper end of the gap through carrier-carrier and carrier-phonon interactions. Then, the carriers emit high-energy phonons (HEPs) whose energies are higher than the gap width 2 to relax into the lower end of the gap.…”
Section: A Description Of the Phonon Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The term pseudogap has been coined to describe this kind of physics. The presence of pseudogap has been established through the measurements of the nuclear magnetic resonance (NMR) [5], the scanning tunneling spectroscopy [6][7][8][9], the analysis of the electronic Raman scattering [10][11][12], through time-resolved optical spectroscopy [13][14][15][16][17][18], and through the ARPES [19][20][21][22][23][24][25]. The observed strong Nernst effect in cuprates has been also attributed to it [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the non-equilibrium dynamics of quantum manybody systems has, in fact, posed a theoretical challenge. Historically, theoretical attempts to model the time evolution of properties have either used quasi-equilibrium models such as T * and µ * models 20 to describe non-equilibrium excitations created by a pump pulse 21 or rate equation approaches based on the phenomenological Rothwarf-Taylor model 22 to describe the recovery dynamics of the superconducting state. Recently, the time evolution of the optical conductivity has been studied within a microscopic model that treats the excitation and relaxation dynamics on the same footing.…”
Section: Introductionmentioning
confidence: 99%